2008
DOI: 10.1002/dvdy.21464
|View full text |Cite
|
Sign up to set email alerts
|

mTOR signaling contributes to chondrocyte differentiation

Abstract: The mammalian Target Of Rapamycin (mTOR) is a nutrient-sensing protein kinase that regulates numerous cellular processes. Fetal rat metatarsal explants were used as a physiological model to study the effect of mTOR inhibition on chondrogenesis. Insulin significantly enhanced their growth. Rapamycin significantly diminished this response to insulin through a selective effect on the hypertrophic zone. Cell proliferation (bromodeoxyuridine incorporation) was unaffected by rapamycin. Similar observations were made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
5
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 52 publications
5
77
5
1
Order By: Relevance
“…[41][42][43] However, in this study, we did not observe frequent activation of mTOR in tumors of smooth muscle cell, adipocyte, or chondrocyte origin in contrast to rhabdomyosarcoma. Probably, the functional involvement of mTOR is different in tumor vs normal tissue, or the involvement of mTOR in those tumors may be transient in the specific stage during oncogenesis.…”
Section: Discussioncontrasting
confidence: 75%
“…[41][42][43] However, in this study, we did not observe frequent activation of mTOR in tumors of smooth muscle cell, adipocyte, or chondrocyte origin in contrast to rhabdomyosarcoma. Probably, the functional involvement of mTOR is different in tumor vs normal tissue, or the involvement of mTOR in those tumors may be transient in the specific stage during oncogenesis.…”
Section: Discussioncontrasting
confidence: 75%
“…Infection of chondrocytes with lentivirus expressing CA MEK reduced both aggrecan mRNA expression and proteoglycan protein synthesis, as did activation of MEK-ERK using tBHP. Negative regulation of proteoglycan production by activated MEK-ERK has been previously observed during chondrogenesis in embryonic chick limb bud cultures (50), and inhibition of MEK-ERK has been found to promote chondrocytic differentiation of ATDC5 cells (51) and aggrecan expression in immortalized rat chondrocytes (52). These findings are in contrast to a study of mechanically stimulated bovine calf chondrocytes, where inhibition of MEK-ERK either reduced aggrecan expression or had no effect, depending on the stimulation conditions (53).…”
Section: Discussionmentioning
confidence: 77%
“…Rapamycin, an MTOR inhibitor, decreases longitudinal bone growth and chondrocyte hypertrophy. 11,12 Thus, it is plausible to assume that activation of MTORC1 leads to increased chondrocyte hypertrophy and bone growth. Supporting this we found that the MTOR inhibitor Torin1 attenuates Baf-and CQ-induced bone growth.…”
Section: Inhibition Of Lysosomes and Bone Growthmentioning
confidence: 99%
“…10 Rapamycin, an MTOR inhibitor which mainly disrupts MTORC1 activity, 1 inhibits bone growth both in vitro and in vivo. 11,12 Conditional ablation of RPTOR in the limb (using periaxin [Prx]-driven Cre) reduces limb size and hypertrophic chondrocyte cell size. 13 Furthermore, MTORC1 was proposed to regulate the transition of chondrocytes from the proliferative to the post-mitotic stage of maturation.…”
Section: Introductionmentioning
confidence: 99%